Pengaruh Persepsi Wajib Pajak Atas Pelayanan Kpp, Sanksi Perpajakan dan Pengetahuan atas Penghasilan Kena Pajak terhadap Kepatuhan Wajib Pajak - Afrizal Tahar; Wilie Sandy (Universitas Muhammadiyah Yogyakarta, Indonesia, 2011)
The efforts of increasing tax income has become a special intention for the government, one of the efforts is enhancing taxpayer’s compliance in fulfilling the tax duty. This research is aimed to know whether taxpayer’s perception of the service in tax service office, tax sanction and the knowledge about taxable income affect the taxpayer’s compliance. The research used primary data by distributing questionnaires to the personal taxpayers that registered in Tax Service Office Pratama Bantul. Data that collected then processed using multiple regressions with SPSS (Statistical Package for Social Science) program.The r esult of research showed that taxpayer’s perception of the service in tax service office impacted significantly to the taxpayer’s compliance. The knowledge about taxable income also impacted significantly to the taxpayer’s compliance. However, tax sanction does not impacted significantly to the taxpayer’s compliance. Many Taxpayers are still do not know and understand about tax sanction in taxation. This becomes a job for tax office to socialize tax sanction to society.